Analisis Pengaturan Sanksi Pidana terhadap Anak Pelaku Tindak Pidana Perundungan - Ahmad Affandi; Muhammad Islahuddin (AHKAM, 2025)
This study is driven by the increasing prevalence of bullying cases committed by minors in Indonesia, which not only affect the victims but also raise legal issues concerning the regulation of criminal sanctions. The aim of the research is to analyze the regulation of criminal sanctions against child perpetrators of bullying under Indonesia’s positive law and to assess its alignment with child protection principles. The research employs a normative juridical method using a statute approach and a conceptual approach. Data sources include primary legal materials in the form of legislation and secondary legal materials such as literature, journals, and previous studies. The data were analyzed qualitatively through legal interpretation techniques. The findings indicate that the regulation of criminal sanctions for child perpetrators of bullying is stipulated in Law No. 11 of 2012 on the Juvenile Criminal Justice System and other related regulations, which prioritize rehabilitative measures over imprisonment. This approach aligns with the principle of the best interest of the child, although its implementation faces challenges such as limited rehabilitation facilities, a shortage of support personnel, and suboptimal application of diversion. The study contributes to juvenile criminal law literature by emphasizing the importance of harmonizing law enforcement with child protection. Recommendations include strengthening technical regulations, enhancing the capacity of law enforcement officers, and improving oversight of the implementation of rehabilitation policies for child perpetrators of bullying.